ANALYSIS OF FACTORS THAT INFLUENCE PEOPLE’S BEHAVIOR TOWARDS ANTIGEN SWAB SERVICES - Dian Sari; Novita Br Ginting Munthe (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
One of the measures to prevent the transmission of COVID-19 is the examination of an antigen swab. Data from Tanjung Morawa Village, Deli Serdang Regency in January-June 2022 from 17800 people who were positive for COVID-19 as many as 259 people (1.4%). This study aims to determine the analysis of the factors that influence people's behavior towards the antigen swab service at the Hamidah Tanjung Morawa Clinic, Deli Serdang Regency in 2022. The study used a quantitative type of observational research with a cross-sectional design. The population is the number of people in Tanjung Morawa Village, Deli Serdang Regency as many as 17800 people. The sample is 99 people with random sampling technique. Data analysis was carried out with univariate analysis, bivariate with Chi-Squre test and multivariate with multiple logistic regression test. The results showed that from 99 people the majority of the education was in the low category, namely 51 people (51.5%), knowledge was in the poor category, 50 people (50.5%), the attitude was in the negative category, namely 56 people (56.6%), the belief category was not sure. namely 57 people (57.6%), sources of information in the direct category are 56 people (56.6%), family support in the unsupportive category is 55 people (55.6%), the support from community leaders in the unsupportive category is 65 people (65 ,7%), the support of health workers in the supportive category was 61 people (61.6%) and the behavior of the community towards the antigen swab service in the non-category category was 51 people (51.5%). The conclusion that there is education (p = 0.000), economic status (p = 0.000), knowledge (p = 0.000), attitudes (p = 0.001), beliefs (p = 0.000), sources of information (p = 0.000), family support ( p = 0.001), support from community leaders (p = 0.002), support from health workers (p = 0.000) on community behavior in the antigen swab service at the Hamidah Tanjung Morawa Clinic, Deli Serdang Regency. The results of the multivariate variable that most influence the behavior of the antigen swab service community is knowledge. It is recommended that the community apply good community behavior in the antigen swab service to provide benefits in controlling the Covid-19 infection outbreak.